WEED MANAGEMENT IN DIRECT SEEDED RICE - S. Hussain; M. Ramzan; M. Akhter; M. Aslam (Journal of Animal and Plant Sciences, 2008)
To manage the weeds in direct seeded rice, four weedicides were tested and compared their efficacy with handweeding. Among the weedicides Nominee 100SC (bispyribac sodium) and Sunstar Gold 60WG (Ethoxy sulfuron) proved as the best weedicides with 90.5 and 87.19% weed control respectively. The paddy yield in both the weedicide treatments was also comparatively higher than other weedicides. The highest net benefit was obtained by the application of nominee 100sc followed by Sunstar Gold 60 wG treatment while the lowest net benefit was provided by control (weedy check). No doubt, the results of hand weeding are significantly better but as it is time consuming and laborious hence cannot be recommended at large scale.
Keywords: Direct seeding; weedicides; hand weeding; weed density; rice